Jump capacity and the ACL injury in female handball players - Estriga, L.; Carvalho, J.; Bernardes, J.; Massada, L. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The risk of ACL injuries seems to be higher in adolescents and young female athletes in comparison to male athletes of the same age. In handball, the lower limb muscle strength is essential to perform faking movements, changes in direction, accelerations and jumps. These actions are also the most frequently implicated in the ACL injuries mechanism. Purposes: to examine the influence of maturation, oral contraceptive status, previous knee injuries and handball exposure in jump performance. Sample: 496 Portuguese female handball players, 16±4 years old, practicing handball for 6±5 years. A cross-sectional experimental design was employed in the 2006-07 season. The testing sessions included initial anthropometric measurements, including standing body height, body mass and percentage of fat mass (by bioelectrical impedance). A screening questionnaire was used to assess some vital data, previous knee injuries and sports related information. Vertical jump tests were used to assess lower limb muscle strength: the squat jump (SJ) and counter-movement jump (CMJ). A contact platform was used to assess the height jumped. The m-eccentric utilization ratio (mEUR) was defined as CMJ/SJ-1. Results: A stepwise regression on the jump performance revealed that there is a significant dependence only on age, BMI and field position (p<3%). The dependence on age is well described by 3rd degree polynomials (r2>79%) with a minimum at the start of the series (10 years) and a maximum at about 28 years. However, the CMJ and SJ evolve similarly (r2=0.75), what means that the elastic energy utilization, a frequent indicator of jump competence, has no significant trend during the players careers (r2=0.03). This is unexpected and in contrast with published data. We have found a small increase in jump performance around the menarche age, not different from other improvements during other phases of the players` careers (average of 5cm in 4 years). On BMI, the jump performance dependence is less clear. Both CMJ and SJ are best described by parabolas with peaks at around 22.6kg/m2 but the fits have low adherence (r2>40%). They are also almost parallel along all range. There is a statistical relation between field position and jump capacity. While left and right back players, as well as left-wingers, tend to have the higher jump capacities, pivots and right-wingers tend to be on the opposite extreme. Finally, we have observed that players without previous knee injuries have a lower SJ capacity than players with previous knee injuries (p<4%). Conclusions:Maturation per se is not has decisive on jumping performance as training. The absolute jumping capacity, the mEUR values and it`s evolution along ages may all be interpreted as a sign of a conditionally under trained population, possible at higher risk of ACL injury due to low dynamic knee stabilization capabilities. Hormonal therapy does not have a significant effect on jumping performance.